Mathematical beliefs: What topics appear, and how has this changed over time? - Muhtarom, Muhtarom; Nizaruddin, Nizaruddin; Sutrisno, Sutrisno; Murtianto, Yanuar Hery; Baldemor, Milagros (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
This research uses the Systematic Mapping Study (SMS) method to identify knowledge trends in beliefs about the nature of mathematics, learning, and learning mathematics and identify new development opportunities for further research. The Systematic Mapping Study (SMS) method is the initial stage for selecting primary sources in a literature study. The Scopus database was used for SMS, then 171 articles were found ready for further analysis. The results show that mathematical belief has become a current research trend. The keywords are "beliefs." The new trending keyword is "pre-service teachers." The thematic map shows thirteen clusters, where the motivation, pre-service mathematics teachers, mathematics education, beliefs, and attitudes clusters are the motor themes currently a global challenge. This means there are still great opportunities to research this theme to complete the knowledge puzzle. In closing, 41 articles are primary articles related to this theme. Three of them, namely articles from Stipek et al. (2001), Beswick (2012), and Felbrich et al. (2012), can be seen as primary references.